Formulation Parameters Characterization & Comparative Study Of Carbamazepine Tablets - SHAIKH ANIS; KHAN RIZWAN; JADHAV JATIN; BHARGAVA TANU (International Journal of Pharma and Bio Sciences, 2012)
This research analyses the concept of formulations in epilepsy and evaluates marketed available formulations of carbamazepine. ER formulations are usually designed to reduce dose frequency and maintain relatively constant or flat plasma drug concentration. Epilepsy is a single-episode disease, and the convenience and possible better compliance associated with once-daily administration must be weighed against the shorter ’forgiveness’ period and possible higher risk of breakthrough seizure due to sub-therapeutic plasma levels and/or omitted doses. Several literature reports show that up to 30% of epileptic patients may not respond to drug therapy, or inadequate control of their seizures, even if there is increasing prevalence and incidence rates of epilepsy. In this investigation, trial has been undertaken for the prediction of the reasons of treatment failures by virtue of controlling the drug quality aspects. Evaluation studies provide a means of identifying quality differences between same products obtained from various manufacturers. Quality analysis and evaluations are the most important tasks to be performed when various reports of therapy indicate problems and failures of treatment. Data suggest that all the tablets met the quality specification with respect to hardness, friability, disintegration, dissolution, assay and dosage form uniformity (weight variation and/or content uniformity). With respect to drug content (assay), from the carbamazepine tablets analyzed, ZEN was found to be out of the specified tolerance limit, while the other carbamazepine tablets evaluated were within the tolerance limits of content.